Carbon fraction distribution of soil depths of omo biosphere reserve, Nigeria. (2019)
Soil is regarded as largest carbon reservoir in terrestrial ecosystem but availability of information on soil aggregates cum carbon fraction distribution along depths in relation to specified location is lacking. Soil carbon accumulation of aggregate sizes was estimated at five soil depths in natural forest reserve, Omo Biosphere Reserve, Nigeria. Guided by the heterogeneity of the reserve, it was stratified into close and open canopy structures. Fourteen and six (30m x 30m) sample plots were demarcated in close and open canopy, respectively. Profile pit was dug at the center of sample plots (30m x 30m) and soil samples were collected at 0-20, 20-40, 40-60, 60-80, 80-100cm depths and air dried. Air- dried soil samples (100g) were separated into five aggregate sizes (>2.0, 2-1, 1-0.5, 0.5-0.052mm, <0.052mm) using wet sieving method, and percentage carbon content of each aggregate fractions were determined using Loss on Ignition Method. Data collected were analyzed using descriptive statistics and ANOVA at dos. Carbon distribution varied among the soil aggregates and across the depths. The degree of carbon protection and carbon stability are higher in <0.052mm aggregate size than in other aggregates. Macro-aggregate and micro-aggregate are responsible for carbon accumulation in surface and sub-surface soils, respectively. Therefore, macro-aggregate and micro-aggregate are responsible for carbon sequestration in soil of Omo Biosphere Reserve.